ANALISIS STAKEHOLDERS DALAM FORMULASI KEBIJAKAN KOTA LAYAK ANAK DI KOTA SEMARANG - Andriyanto, Ferdy; Purnaweni, Hartuti (Journal of Public Policy and Management Review, 2017)
The number of issues related to violence against children in city of Semaranghad reached up to 1474 case, drawing attention to Semarang city government to immediately make effort of restraint cases of violence against children. To date, Semarang city government still experiencing difficulties in dealing withcases of violence against children in city of Semarang. Consequently, Policy of eligible children was formulated through Mayor’s regulation Number 20 Year 2010 and Mayor’s decree Number 124 Year 2011 regarding task force formation of worthy cities of children in city of Semarang. The purpose of this study is to understand and analyze influence and interests, commitment, participation of each stakeholders and relation between each stakeholder’s task force of Semarang’s worthy cities of children in policy formulation eligible children in Semarang. This study usedqualitative research methods approach. Data collected through interviews, observation and study of documentation. Furthermore, data analysis done through data reduction, data presentation and conclusion. Research showed that in the Child-Friendly City policy formulation process involving the Bappeda, Bapermasper, KB, Yayasan Setara and KADIN is not going well. This can be seen from Bappeda, Bapermasper, KB and KADIN’s not optimal commitment. Then Bappeda and Bapermasper and KB have a great influence and interests because they have planning and coordination functions. Yayasan Setara don’t have a great influence but have great interests. While KADIN’s don’t have a great influence and interests.